The Effect of The Determination of Plant Quarantine Installations and Inline Inspections On The Acceleration of Agricultural Commodity Exports In The Working Area of The Surabaya Agricultural Quarantine Center - Veny Octoraningtyas (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to determine the impact of establishing plant quarantine facilities and inline inspection on export acceleration at the Surabaya Plant Quarantine Center. The study employs a quantitative approach and collects data from agricultural export companies operating in regions that implement plant quarantine measures and inline inspection. The analysis method used in this research is the Kruskal-Wallis test to evaluate the relationship between the establishment of plant quarantine facilities and inline inspection and export acceleration. The results of the analysis indicate a significant influence of establishing plant quarantine facilities and inline inspection on export acceleration. Export companies registered with effective Plant Quarantine Facilities and inline inspection demonstrate an improvement in their ability to meet plant quarantine requirements and enhance efficiency in inline inspections. This positively impacts the export process, including reducing delays and increasing the confidence of international trading partners. This research provides a better understanding of the role of plant quarantine facilities and inline inspection in driving ean xport acceleration in the agricultural sector. The practical implications of this study emphasize the importance of enhancing plant quarantine infrastructure and implementing effective inline inspection systems to promote agricultural export growth. Moving forward, efforts should be made to improve coordination among relevant agencies in the implementation and supervision of plant quarantine and inline inspection regulations to achieve optimal outcomes in enhancing the export performance of the agricultural sector.